Integrated transversal equalizers in high-speed fiber-optic systems. - Hui Wu
Intersymbol interference (ISI) caused by intermodal dispersion in multimode fibers is the major limiting factor in the achievable data rate or transmission distance in high-speed multimode fiber-optic links for local area networks applications. Compared with optical-domain and other electrical-domain dispersion compensation methods, equalization with transversal filters based on distributed circuit techniques presents a cost-effective and low-power solution. The design of integrated distributed transversal equalizers is described in detail with focus on delay lines and gain stages. This seven-tap distributed transversal equalizer prototype has been implemented in a commercial 0.18-μm SiGe BiCMOS process for 10-Gb/s multimode fiber-optic links. A seven-tap distributed transversal equalizer reduces the ISI of a 10-Gb/s signal after 800 m of 50-μm multimode fiber from 5 to 1.38 dB, and improves the bit-error rate from about 10-5 to less than 10-12.
Keywords: 0.18 micron; 5 to 1.38 dB; 800 m; SiGe BiCMOS process; Bit-error rate; Cost-effective solution; Data rate; Delay lines; Distributed circuit techniques; Electrical-domain dispersion compensation; Fiber-optic communications; Gain stages; High-speed fiber-optic systems; Integrated distributed transversal equalizers; Integrated transversal equalizers; Intermodal dispersion; Intersymbol interference; Local area networks applications; Low-power solution; Multimode fiber-optic links; Multimode fibers; Optical-domain dispersion compensation; Seven-tap distributed transversal equalizer; Transmission distance; Transversal filter equalization